Effect Of Cellulosic Material From Oil Palm Empty Fruit Bunches (Opefb) On The Reinforcement Properties Of Recycled Paper - Rahman, Khairul Hafizuddin Abdul (2017)
The use of recycled fibers in the Malaysian paper industry has been an economic and environmental necessity due to the limited availability of virgin fiber. However, with each recycling, the paper strength decreases, hence different methods are employed to increase its strength potentials. Various forms of oil palm cellulosic materials viz. OPEFB-UB, OPEFB-OZP, OPEFB-MCC and OPEFB-TEMPO were used to enhanced the strength properties of the recycled paper that were obtained from the old corrugated container (OCC). The reinforcement potential of the cellulosic materials was compared by an evaluation of the tensile-percent addition relationship which shows that all OPEFB cellulosic materials gave a positive impact with strong correlations as indicative from the R2 values of almost 1. Amongst the four types of OPEFB cellulosics, OPEFB-TEMPO has the greatest potential, followed by OPEFB-MCC, OPEFB-UB and OPEFB-OZP.